Estimating shadow economy size in Greece 2000-2018: A flexible MIMIC approach - Paraskevi Koufopoulou; Colin C. Williams; Athanassios Vozikis; Kyriakos Souliotis; Antonios Samprakos (SPOUDAI - Journal of Economics and Business, 2021)
Greek economy suffers from economic crisis for over a decade. A continuing problem has been the persistence of a large shadow economy which results in a gap between the tax and social security contribution owed and collected. In this paper, the size of shadow economy (SE) in Greece is estimated using a flexible MIMIC approach with time series data from 2000 to 2018. Our variables focused on instead of in most representative data of the Greek economy as causes (e.g. unemployment, self-employment, epidemic etc.) and indicators (official economy, energy consumption, income inequality and poverty, labour force participation). We found that the average size of shadow economy in Greece was up to 37.63% for the reference period, above the average size of other studies up to 23.35%. The study focuses on the significance of each determinant of the shadow economy, resulting in an improved estimation method to identify and tackle shadow transactions and increase public revenues.
Keywords: O17; C20; D73; E26; 330; Greek economy; shadow economy; estimation; flexible MIMIC Model